Human capital as a key element supporting innovation in regions - Łuczyszyn, Tomasz (Kapitał ludzki jako kluczowy element wspierający innowacje w regionach, 2025)
Aim: The aim of the article was to theoretically analyse the importance of human capital and innovation in the process of regional development within the framework of a knowledge-based economy. Methodology: The article employs a literature review and a descriptive method to explore the relationship between human capital and the ability of regions to introduce innovations. Results: Human capital – defined as the knowledge, skills, experience, and creativity of a region's inhabitants – plays a key role in innovation processes. Regions with well-developed human capital demonstrate greater potential for implementing innovations, which strengthens their competitiveness and fosters economic growth. Implications and recommendations: Strengthening human capital should be a priority in regional policy. Investment in education, skills development, and fostering creativity enhances a region's ability to generate and apply innovations effectively. Originality/value: The article provides added value by highlighting the fundamental role of human capital as a driver of innovation and regional competitiveness in the modern knowledge-based economy.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 200-210
Keywords: human capital; innovation; regions; innowacja; badania; konkurencja regionów